Geographical and life-history traits associated with low and high species richness across angiosperm families - Ferrer, Miriam Monserrat; Vásquez-Cruz, Marilyn; Hernández-Hernández, Tania; Good, Sara V. (Frontiers in Plant Science, 2023)
The phenomenal expansion of angiosperms has prompted many investigations into the factors driving their diversification, but there remain significant gaps in our understanding of flowering plant species diversity. Using the crown age of families from five studies, we used a maximum likelihood approach to classify families as having poor, predicted or high species richness (SR) using strict consensus criterion across studies. Using these categories, we looked for associations between family SR and i) the presence of an inferred familial ancestral polyploidization event, ii) 23 life history and floral traits compiled from previously published datasets and papers, and iii) sexual system (dioecy) or genetically determined self-incompatibility (SI) mating system using an updated version of our own database and iv) geographic distribution using a new database describing the global distribution of plant species/families across realms and biomes and inferred range. We find that more than a third of angiosperm families (65%) had predicted SR, a large number of families (30.2%) were species poor, while few (4.8%) families had high SR. Families with poor SR were less likely to have undergone an ancestral polyploidization event, exhibited deficits in diverse traits, and were more likely to have unknown breeding systems and to be found in only one or few biomes and realms, especially the Afrotropics or Australasia. On the other hand, families with high SR were more likely to have animal mediated pollination or dispersal, are enriched for epiphytes and taxa with an annual life history, and were more likely to harbour sporophytic SI systems. These results are discussed within the context of the literature describing "depauperons" and the factors contributing to low and high biodiversity in angiosperm clades.